An overview of the clinical management of cyclic vomiting syndrome in childhood. (3rd October 2018) - Romano, Claudio; Dipasquale, Valeria; Rybak, Anna; Comito, Donatella; Borrelli, Osvaldo
Abstract: This narrative review provides an update on cyclic vomiting syndrome pathogenesis, diagnosis and management, based upon studies published after the 2008 North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) official recommendations. The review began with a comprehensive PubMed/Medline search for "cyclic vomiting syndrome", "periodic syndromes" and "pediatrics" from 2000 up to October 2017. Additional papers were identified by reviewing the re-ference lists of retrieved publications. Cyclic vomiting syndrome is a severe, debilitating disorder of the brain–gut axis with unclear pathogenesis, that significantly affects long-term quality of life of affected children and their families. The 2008 NASPGHAN recommendations defined the major clinical, diagnostic and therapeutic peculiarities. Over the last 10 years, advancements in pathogenesis and diagnostic criteria have been made, and new prophylactic and therapeutic strategies have been proposed. These aspects are discussed in this manuscript. For the pediatrician, the major aim is to have early clinical suspicion to avoid diagnostic delay and to start adequate, phase-related, symptom-tailored management.